2016
DOI: 10.1038/srep29946
|View full text |Cite
|
Sign up to set email alerts
|

Additive reductions in zebrafish PRPS1 activity result in a spectrum of deficiencies modeling several human PRPS1-associated diseases

Abstract: Phosphoribosyl pyrophosphate synthetase-1 (PRPS1) is a key enzyme in nucleotide biosynthesis, and mutations in PRPS1 are found in several human diseases including nonsyndromic sensorineural deafness, Charcot-Marie-Tooth disease-5, and Arts Syndrome. We utilized zebrafish as a model to confirm that mutations in PRPS1 result in phenotypic deficiencies in zebrafish similar to those in the associated human diseases. We found two paralogs in zebrafish, prps1a and prps1b and characterized each paralogous mutant indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…With these stable mutants, a deeper understanding of the mechanisms underlying this reduction of hair cell count could be established. Pei et al (2016) reported a reduced number of hair cells in lateral line neuromasts in prps1a mutants, which is consistent with our findings of reduced inner ear hair cells in the present study. However, they did not find such phenotype in prps1b mutants.…”
Section: Zebrafish Model For Dfx1supporting
confidence: 94%
“…With these stable mutants, a deeper understanding of the mechanisms underlying this reduction of hair cell count could be established. Pei et al (2016) reported a reduced number of hair cells in lateral line neuromasts in prps1a mutants, which is consistent with our findings of reduced inner ear hair cells in the present study. However, they did not find such phenotype in prps1b mutants.…”
Section: Zebrafish Model For Dfx1supporting
confidence: 94%
“…Hair cell staining and quantification were as described (53). Briefly, for analyzing hair cell development, embryos from heterozygotic incrosses were cultured until 5 dpf, and then placed in a cell strainer (BD Falcon) for staining with 2 µM YoPro-1 for 30 minutes.…”
Section: Hair Cell and Neuromast Quantificationmentioning
confidence: 99%
“…Interestingly, while PRPS2 is non-essential for development, PRPS2 knockout mice are resistant to Eµ-Myc-driven cancer development, suggesting that PRPS2 is specifically required for tumorigenesis (Cunningham et al 2014). A zebrafish model of PRPS deficiency has also been recently generated (Pei et al 2016). The prps1a and prps1b double mutant animals fail to properly develop but show some phenotypic similarity to human PRPS1-associated diseases.…”
Section: Introductionmentioning
confidence: 99%